BD Veritor System Respiratory Syncytial Virus Rapid Antigen Detection Test: Point-of-Care Results in Primary Care Pediatric Offices Compared With Reverse Transcriptase Polymerase Chain Reaction and Viral Culture Methods - Schwartz, Richard H; Selvarangan, Rangaraj; Zissman, Edward N (Pediatric emergency care, 2015)
During respiratory syncytial virus season, many children present to pediatric offices and urgent care medical facilities with cough, tachypnea, intercostal retraction, wheezing, as well as disturbed appetite and sleep. Identification of the responsible viral pathogen is quite difficult because several pathogens can produce similar signs and symptoms. Nasopharyngeal specimens were collected from symptomatic sick children younger than 6 years, in 8 geographically representative primary care pediatric practices during a 4-month RSV season. Institutional review board approval and signed parental consent were obtained. The primary objective of the study was the estimation of the sensitivity and specificity of the Becton Dickinson (BD) Veritor RSV point-of-care (POC) assay as compared with reverse transcriptase-polymerase chain reaction (RT-PCR). Of 523 specimens, 58.3% (n = 305) were from patients younger than 2 years. The BD Veritor RSV POC assay sensitivity and specificity are 81.6% (146/179) and 99.1% (341/344), respectively. When compared with RT-PCR, the BD Veritor RSV POC assay false positive was 0.9% (3/344, with a 95% confidence interval of 0.3%-2.5%) and the false negative was 18.4% (33/179, with a 95% confidence interval of 13.4%-24.5%). The BD Veritor RSV POC assay identified more true positive specimens (n = 146) than viral cell culture (n = 134 positive specimens). In 8 participating primary care pediatric offices with 523 evaluable subjects, POC BD Veritor RSV tests performed better than viral cell culture results when RT-PCR was the reference standard.